Emission-reduction investment strategies in competitive shipping supply chains under carbon cap-and-trade mechanisms - Zhang, Guangsheng; Zhang, Zhaomin; Yuan, Hao; Chen, Weijie (Frontiers in Marine Science, 2025)
Market-based carbon cap-and-trade mechanisms play a pivotal role in reducing the carbon emissions of shipping logistics companies. Focusing on the issue of emission reduction investment in the competitive shipping logistics service supply chain (SLSSCs) under carbon cap-and-trade, this paper constructs a game theory model for emission reduction investment decision-making in the SLSSC, which comprises two participants-a shipping logistics service provider (SLSP) and a shipping logistics service integrator (SLSI)-discusses the equilibrium strategy of emission reduction investment based on optimization theory, and further explores the benefits of participating entities, consumer surplus, and social welfare under different emission reduction strategies. The findings indicate that: (1) a no-reduction investment strategy, a single-chain investment strategy, and a dual-chain investment strategy can each serve as equilibrium strategies, which are influenced by the interplay among the unit carbon emission trading price, the spillover effect of emission reduction investments, and the associated cost coefficient. (2) Both single-chain and dual-chain emission reduction strategies in the SLSSCs contribute to consumer surplus; however, their impact on social welfare is contingent on the SLSI’s cost coefficient for emission reductionn investments. (3) Under the single-chain equilibrium strategy, the spillover effect from the SLSI’s emission reduction investment has a favorable impact on returns for participants in the non-investing chain, consumer surplus, and social welfare, but adversely affectts returns for participants in the investing chain. Under the dual-chain equilibrium strategy, the spillover effect benefits both chains’ participants’ returns, consumer surplus, and social welfare. In addition, the SLSP’s altruistic inclination enhances participants’ returns, consumer surplus, and social welfare across all strategies.